Sir Cloudesley Shovell, amiral de la Flotte britannique : engagement patriotique, sacrifice héroïque, mensonge historique - Hélène PALMA (E-REA)
Cloudesley Shovell, a British admiral of the early 18th century was at the head of the British Fleet in 1707 during the Siege of Toulon (War of the Spanish Succession). On their way back home, the four warships of the Fleet hit rocks in the Scilly Islands. All the members of the crew perished. This naval catastrophe, the worst in British history, became an opportunity to create a myth around the 1707 Siege of Toulon and turn Shovell into an iconic figure.